Consistency between household-level consumption data from registers and surveys - Kim Abildgren; Andreas Kuchler; America Solange Lohmann Rasmussen; Henrik Sejerbo Sørensen (Danmarks Nationalbank, 2018)
We explore the consistency at household-level between register-imputed and survey-based consumption figures for Denmark over the period 2002-15. Furthermore, we analyse the differences between consumption functions estimated on the basis of the two types of microdata. We find that there is a close match regarding the median and mean level of consumption reported for the same households in the register-imputed and survey-based consumption data. Furthermore, we find that the marginal propensities to consume out of income estimated for the pre-crisis period (2005-07), the crisis period (2008-11) and the post-crisis period (2012-15) on the basis of register data are not significantly different to those estimated on the basis of survey data for the same households with income levels around the median. Finally, we find a relatively close match between total private consumption in the national-accounts statistics and the register-based consumption figures aggregated over all households. Overall, the findings confirm that low-cost consumption microdata derived from administrative registers covering the entire population of households can be an attractive alternative to survey data.
Keywords: C81; D12; E21; 330; Household microdata; consumption measures; consumption function